Research recast(ed): S1E14 - The Edmonton Queer History Project with Dr. Kris Wells, Dr. Michelle Lavoie and Darrin Hagen - Ekelund, Brittany; Cave, Dylan; Wells, Kristopher; Lavoie, Michelle; Hagen, Darrin (My University, 2022)
Today we learn about Edmonton’s queer history with Dr. Kristopher Wells, Darrin Hagen and Dr. Michelle Lavoie as we get a behind-the-scenes look at the Edmonton Queer History project, which will launch on March 8. We cover the project's new Map and walking tour of downtown Edmonton and learn about the process of finding, exploring and preserving the people and voices from the city's queer history. We will also have two special call-ins from team members Japkaran Saroya and Rob Browatzke as they share what this project meant to them. For now, you can find maps at all branches of the Edmonton Public Library and the Pride Centre of Edmonton. If you have something you’d like to share, please send your stories and histories to Edmontonqueerhistoryproject@gmail.com. To learn more about the Pisces Bathhouse Raid, and more of Edmonton’s queer history through Darrin’s work hosted on the City as Museum Project website.
Keywords: queer history; Edmonton